answersLogoWhite

0


Best Answer

x/3+2=6

first, multiply everything by 3, to get rid of the fraction.

x + 6 = 18

Then subtract the 6 from the left and subtract from the right.

x = 12

and there you have it

User Avatar

Rebekah Hershberger

Lvl 4
โˆ™ 2021-10-02 22:41:07
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards

J's study guide

2 cards

What is the name of Steve on minecraft's name

What is love

โžก๏ธ
See all cards

Steel Tip Darts Out Chart

96 cards

170

169

168

167

โžก๏ธ
See all cards

Add your answer:

Earn +20 pts
Q: If x/3 + 2 = 6 then what is x?
Write your answer...
Submit
Related questions

What is the solution to x cube -4 equals 2?

X3 - 4 = 2 X3 = 6 X = 61/3 X = about 1.817


Factor x3 plus 2x2 plus 3x plus 6?

x3 + 2x2 + 3x + 6 = x2(x + 2) + 3(x + 2) = (x + 2)(x2 + 3)


How do you write x3 plus 2x2-5x-6 in factored form?

x3 + 2x2 - 5x - 6 = x3 + x2 + x2 + x - 6x - 6 = x2(x + 1) + x(x + 1) - 6(x + 1) = (x + 1)(x2 + x - 6) = (x + 1)(x2 + 3x - 2x - 6) = (x + 1)[x(x + 3) - 2(x + 3)] = (x + 1)(x + 3)(x - 2)


X3 plus 6x2 - 4x - 24 factor completely?

x3 + 6x2 - 4x - 24 = (x + 6)(x2 - 4) = (x + 6)(x + 2)(x - 2)


What is the factor for x3 plus 2x2-3x-6?

x3 + 2x2 - 3x - 6 = (x2 - 3)(x + 2)


What is x3-2x2 plus 3x-6 factored out?

(x-2)(x^2+3)


What is the answer to x4 plus x3 minus 14x2 plus 4x plus 6 divided by x minus 3?

The answer to x4+x3-14x2+4x+6 divided by x-3 is x3+4x2-2x-2


What is the factor tree for 72?

72 ---> 2 x 36 2x36 ---> 2 x 6 x6 2 x 6 x6 ---> 2 x 3 x 3x 3 -x3 good luck


What is a polynomial with a single root at x equals -6 and a double root at x equals -4?

-2


How do you factor x3-4x2-20x plus 48?

(x - 2)(x + 4)(x - 6)


Is x-2 a factor of x3-6x2 11x-6?

Yes.


How to Factor x3 plus 4x2 plus 7x plus 6?

(x + 2)(x^2 + 2x + 3)


How do you factor x cubed minus four x squared plus x plus 6?

x3 - 4x2 + x + 6 The sum of the odd coefficients equals the sum of the even coefficients, so (x + 1) is a factor. So x3 - 4x2 + x + 6 = x3 + x2 - 5x2 - 5x + 6x + 6 = x2(x + 1) - 5x(x + 1) + 6(x + 1) = (x + 1)(x2 - 5x + 6) = (x + 1)(x - 2)(x - 3)


What is x cubed minus 4x squared plus x plus 6 when fully factorized?

x3 - 4x2 + x + 6 = (x + 1)(x - 2)(x - 3)


How do you solve x cubed minus 4 equals 2?

x3-4=2 Add four to both sides. x3=6 Take the cu=6 be root of both sides. x is equal to the cube root of 6, or approximately 1.81712.


What is x3 - x2 plus x - 2 factored?

x3 - x2 + x - 2 has no rational factors.


Factor the polynomial x3-2x2 plus x-2?

x3 - 2x2 + x - 2 =(x - 2)(x2 + 1)


How do you factor x3-2?

There is no factorisation for x3-2 nor for x^3-2.


What is the factorization of the trinomial- x3 plus 13x2 plus 42x?

x3 + 13x2 + 42x = x(x + 6)(x + 7).


How do you get the cube of binomials?

(x+2)3 =(x)3+3(x)2(2)+3(x)(2)2+(2)3 =x3+6x2+12x+6


Factor x3 plus 8?

x3 + 8 = x3 + 23 = (x + 2)[x2 - (x)(2) + 22] = (x + 2) (x2 - 2x + 4)


What is x when X4 plus 3x3 - x2 - 9x - 6 equals 0?

x4 + 3x3 - x2 - 9x - 6 = 0 x4 + x3 + 2x3 + 2x2 - 3x2 - 3x - 6x - 6 = 0 x3(x + 1) + 2x2(x + 1) - 3x(x + 1) - 6(x + 1) = 0 (x + 1)(x3 + 2x2 - 3x - 6) = 0 (x + 1)[x2(x + 2) - 3(x + 2)] = 0 (x + 1)(x + 2)(x2 - 3) = 0 So x + 1 = 0 so that x = -1 or x + 2 = 0 so that x = -2 or x2 - 3 = 0 so that x = +/- sqrt(3)


Factor Completely x3 plus 8?

x3 + 8 = x3 + 23 = (x + 2)(x2 + 2x + 22) = (x + 2)(x2 + 2x + 4)


How do you factor x3 plus 7x2 plus 18x plus 24?

I know the answer is x(x^2+3x+6) + 4(x^2+3x+6) which factors to (x+4)(x^2+3x+6) but I don't know the rule behind this. Could someone explain it to me?


Solve the equation- X cubed plus 4x squared plus x minus 6 equals 0?

x3 + 4x2 + x - 6 = 0 x3 - x2 + 5x2 - 5x + 6x - 6 = 0 x2(x - 1) + 5x(x - 1) + 6(x - 1) = 0 (x - 1)(x2 + 5x + 6) = 0 (x - 1)(x + 2)(x + 3) = 0 So x = 1 or x = -2 or x = -3